Investigating the role of deep weathering in critical zone evolution by reactive transport modeling of the geochemical composition of deep fracture water. (1st November 2021) - Ackerer, J.; Ranchoux, C.; Lucas, Y.; Viville, D.; Clément, A.; Fritz, B.; Lerouge, C.; Schäfer, G.; Chabaux, F.
Abstract: Relatively little is known about the deep water circulation and the role of deep weathering processes on the Critical Zone (CZ) evolution. In this study, major fractures from four deep boreholes and water collected from these fractures (20–60 m of depth) were studied to improve our understanding of the deep CZ in a granitic headwater watershed (Strengbach watershed, France). Geochemical analysis indicates that chemical composition of deep water (20–60 m) is clearly different than shallow subsurface waters (0–15 m), with higher mean concentrations and a stronger spatial variability across the watershed. Reactive-transport modeling performed with the 1D KIRMAT code (KInetic of Reaction and MAss Transport) highlights the role of minor mineral dissolution (i.e. dolomite) and of longer mean transit time (100–597 yr) along fractures for explaining these differences. The obtained results also shed light on the difference of hydrogeochemical functioning between shallow subsurface system (water sampled from springs and piezometers) and deep system (deep water from borehole fractures). The shallow subsurface system (0–15 m) is characterized by a spatially relatively homogeneous water flow, high mean pore velocities, and water–rock interactions in a porous regolith, while the deep water circulation (20–60 m) behaves much more as independent systems along fractures, with low mean pore velocities, and variable mineralogy and hydrodynamic conditions. A state of chemical equilibrium can also be reached along fractures in the deep CZ for some primary minerals (biotite and K-feldspar), a feature never observed so far in the simulations of shallow subsurface water chemical composition in the Strengbach watershed. Even if the deep water exhibits higher solute concentrations, significantly lower mean pore velocities inferred in the fractured zones imply that the deep water is responsible for a very small part of the total hydrologic and weathering fluxes in the watershed. The limited role of the deep weathering processes (20–60 m) compared to the shallow subsurface processes (0–15 m) suggests an up to bottom control of the CZ evolution at a millennial timescale. Our results also indicate that the majority of fresh water available for water supply at a human timescale originates from shallow subsurface waters, as the deep water circulation is too low for being critical at a timescale relevant for societal needs in this type of geological context.